2016
DOI: 10.1111/jfpp.12725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roasted Yellow Chickpea (Leblebi) Flour Addition on Chemical, Rheological and Sensory Properties of Boza

Abstract: The effect of yellow chickpea (leblebi) flour substitution with maize, rice or/and wheat flours on chemical, rheological and sensory properties of a fermented cereal product boza was investigated. Boza samples with leblebi flour alone had the highest protein (8.46%), ash (1.107%), Ca (268.1 ppm), K (525.3 ppm), P (199.2 ppm), Zn (3.13 ppm), Mn (1.14 ppm), acidity (0.57%), lactic acid (717.3 mg/100 g) and acetic acid (293.5 mg/100 g), and the lowest sucrose (0.05 g/100 g) contents. Results of rheological analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Chemical compositions of the Turkish boza samples manufactured with various raw materials were previously reported by several authors (Arıcı and Dağlıoğlu, 2002;Çelik et al, 2016). In this study, the chemical compositions of the samples were investigated comparatively based on their raw material compositions.…”
Section: Protein Fat Dietary Fiber Carbohydrate and Alcohol Contents Of Boza Samplesmentioning
confidence: 84%
“…Chemical compositions of the Turkish boza samples manufactured with various raw materials were previously reported by several authors (Arıcı and Dağlıoğlu, 2002;Çelik et al, 2016). In this study, the chemical compositions of the samples were investigated comparatively based on their raw material compositions.…”
Section: Protein Fat Dietary Fiber Carbohydrate and Alcohol Contents Of Boza Samplesmentioning
confidence: 84%
“…Chickpea (Cicer arientum) is one of the most important pulse crops with high carbohydrate and dietary fiber content, considerable protein content and of various minerals (Bibi et al, 2007;Özer et al, 2010;Mafakheri et al, 2011;Torutaeva et al, 2014;Çelik et al, 2016). Due to its high nitrogen utilization efficiency and high protein yield under drought conditions, chickpea is mostly grown in arid or semiarid Mediterranean environment of West Asia and North Africa and adopted in North America, western Canada, Australia, New Zealand, and Central Europe (Oweis et al, 2004;Özer et al, 2010;Ozkilinc et al, 2011;Atalay and Babaoglu, 2012;Siddique et al, 2012;Neugschwandtner et al, 2015;Sadras and Dreccer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its suitable climatic conditions, Turkey is the fifth biggest producer of chickpea after India, Australia, Myanmar, and Ethiopia (FAO, 2012). In the market high yield registered chickpea cultivars resistant or tolerant to biotic and abiotic stress factors are being grown and consumed as flour, canned, roasted, boiled, fermented, fried steamed, or snack food (Coşkuner and Karababa, 2004;Bibi et al, 2007;Özer et al, 2010;Çelik et al, 2016). The studies also showed that chickpea seeds had good functional properties which allowed them to be used as additive in processed foods, cosmetics and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…The major producer of chickpea is India with 9.9 M tones production and followed by Australia, Myanmar, Ethiopia, and Turkey (FAO, 2014). It is the third most important pulse crop after dry bean and pea and consumed as flour, canned, roasted, boiled, fermented, fried steamed, or eaten as snack food (Bibi et al, 2007;Coşkuner and Karababa, 2004;Çelik et al, 2016;Özer et al, 2010). Chickpea is good source of protein (15-29 %), carbohydrate (41-47 %), dietary fiber (14-18 %), minerals and vitamins (Bibi et al, 2007;Çelik et al, 2016;Mafakheri et al, 2011;Özer et al, 2010;Torutaeva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is the third most important pulse crop after dry bean and pea and consumed as flour, canned, roasted, boiled, fermented, fried steamed, or eaten as snack food (Bibi et al, 2007;Coşkuner and Karababa, 2004;Çelik et al, 2016;Özer et al, 2010). Chickpea is good source of protein (15-29 %), carbohydrate (41-47 %), dietary fiber (14-18 %), minerals and vitamins (Bibi et al, 2007;Çelik et al, 2016;Mafakheri et al, 2011;Özer et al, 2010;Torutaeva et al, 2014). However, chickpea is cultivated mostly in arid or semiarid Mediterranean environment of West Asia and North Africa, it has been adopted in North America, western Canada, Australia, New Zealand, and Central Europe due to its high nitrogen utilization efficiency and high protein yield under drought conditions (Neugschwandtner et al, 2015;Oweis et al, 2004;Sadras and Dreccer, 2015;Siddique et al, 2012).…”
Section: Introductionmentioning
confidence: 99%